FAKTOR - FAKTOR YANG MEMPENGARUHI TUMBUH KEMBANG ANAK PADA PEKERJA MIGRAN DI INDONESIA - Nasyifa, Lutfika Arifatun; Kusuma, Inggar Ratna; Lestari, Nadia Citra; 'Aisy, Ba'ats Rihhadatul; Yasmina, Hanum Akmala (SINERGI : Jurnal Riset Ilmiah, 2025)
ABSTRACT Background: The phenomenon of labor migration, particularly by Indonesian Migrant Workers (PMI), creates a dual impact on families: economic improvement versus psychosocial vulnerability in children left behind (Left-Behind Children - LBC). The parental absence triggers changes in parenting patterns, family disharmony, and developmental challenges for LBC across various regions in Indonesia. Objective: To identify, map, and synthesize various factors affecting the growth and development of PMI children in Indonesia, and to identify policy gaps and documented forms of intervention. Methods: This review synthesizes data from 20 articles published between 2017 and 2025. The articles include quantitative studies, qualitative studies, mixed-methods, systematic reviews, and case studies focusing on LBC and their caregivers. Results: The review found that migration creates multidimensional vulnerabilities: 1) Mental Well-being: LBC are at a higher risk of emotional problems, hyperactivity, and behavioral problems. They report higher levels of stress, anxiety, and depression due to the disruption of emotional bonds. However, social support is proven to be positive and significant for the children's subjective well-being. 2) Physical Health: Migration does not significantly affect serious diseases but increases the incidence of minor ailments, especially in children left behind by the father. Children with working parents tend to have a higher prevalence of developmental deviations. 3) Education: LBC tend to have lower cognitive scores, interest, and academic achievement compared to non-migrants due to the lack of attention from core parents and suboptimal parenting patterns. 4) Parenting and Family: Childcare shifts to extended family (relatives) who implement democratic or permissive parenting styles. However, the absence of core parents causes family disharmony and increases the LBC's vulnerability to criminal influences such as brawling and premarital sex. Conclusion: The negative impact of migration on LBC in Indonesia is comprehensive, covering physical, psychological, and academic aspects. Integrated interventions are required, including strengthening the capacity of alternative caregivers, enhancing effective communication, and specific government policy support to protect the basic rights of LBC.